2019
DOI: 10.1097/md.0000000000016652
|View full text |Cite
|
Sign up to set email alerts
|

Pineal region metastasis with intraventricular seeding

Abstract: Introduction: Tumors of the pineal region are rare, and metastatic carcinoma occurring in the pineal region is extremely rare. No previous reports have described pineal region metastasis with intraventricular seeding. Patient concerns: We report a case of a 51-year-old woman presented with a 1-week history of severe headache, nausea, and vomiting. Imaging examination revealed 2 lesions in the pineal region and the right lateral ventricle. Diagnosis: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…[ 2 ] Meningiomas, schwannomas, and ependymoma are the most frequent tumors and others include chordomas and epidermoid cysts. [ 3 ] Metastatic neoplasms located in the foramen magnum are extremely uncommon, because brain metastases are the most commonly found at the junction of the hemispheric gray and white matter. It is reported in the literature that the tumors metastasized to the foramen magnum can come from prostate adenocarcinoma and malignant melanoma, but the tumors from NE cancer have not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Meningiomas, schwannomas, and ependymoma are the most frequent tumors and others include chordomas and epidermoid cysts. [ 3 ] Metastatic neoplasms located in the foramen magnum are extremely uncommon, because brain metastases are the most commonly found at the junction of the hemispheric gray and white matter. It is reported in the literature that the tumors metastasized to the foramen magnum can come from prostate adenocarcinoma and malignant melanoma, but the tumors from NE cancer have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, metastatic neoplasms located in the foramen magnum are extremely uncommon. [ 3 ] Brain metastases are the most commonly found at the junction of the hemispheric gray and white matter. To the best of our knowledge, no studies have reported metastatic large cell NE lung cancer to the foramen magnum.…”
Section: Introductionmentioning
confidence: 99%
“…The pineal gland, or epiphysis cerebri, represents an exceptionally uncommon site of systemic metastasis (1, 2). Indeed, metastasis to the pineal gland is most commonly a derivative of a primary lung malignancy; however, numerous other primary malignancies have been reported to metastasize to the epiphysis cerebri including esophageal, stomach, liver, colon, pancreas, kidney, bladder, prostate, thyroid, breast, melanoma, myeloma, and leukemia (3,4). Considered one of the neuroendocrine secretory circumventricular organs, capillaries of the pineal gland are mostly permeable to solutes in the blood (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although metastasis to the brain is common in the setting of primary malignancies, metastasis specifically to the pineal region is an exceedingly rare phenomenon accounting for 0.4-3.8% of all intracranial metastases (1,2). Metastasis to the pineal gland is most commonly a derivative of a primary lung malignancy; nevertheless, there are reports of a variety of primary tumors that have metastasized to this neuroendocrine secretory circumventricular organ including esophageal, stomach, liver, colon, pancreas, kidney, bladder, prostate, thyroid, breast, melanoma, myeloma, and leukemia (3,4). However, to the best of the authors' knowledge, pineal gland metastasis without a primary origin has yet to be described.…”
Section: Introductionmentioning
confidence: 99%
“…Metastatic cancer spreading to the pineal gland is exceedingly uncommon and originates from lung carcinoma in most cases ( Figure 10 ). Other tumors that have documented cases of metastases to the pineal gland are pancreatic, esophageal and bladder neoplasms [ 110 , 111 , 112 , 113 ].…”
Section: A Brief Overview Of Other Neoplastic and Non-neoplastic Pmentioning
confidence: 99%